Analisis Model Sleiqr Pada Penyebaran Penyakit Covid-19 - Agnes Marselina Nuhan; Roberta Uron Hurit; Irwanius P. Muaraya (Jurnal Media Informatika, 2025)
The objective of this research is to address the SLEIQR mathematical model associated with the transmission of COVID-19 by employing the Euler and Heun numerical techniques. The SLEIQR model is structured as a set of nonlinear differential equations that categorizes the population into six compartments: Susceptible (S), Closed (L), Exposed (E), Infected (I), Quarantined (Q), and Recovered (R). The approach adopted in this research is a literature review combined with a numerical method, wherein simulations are conducted using MATLAB under two distinct scenarios. The findings from the simulations suggest that the application of closure and quarantine measures can diminish the rate of increase in the number of infected individuals. Both methods yield comparable results in terms of solution behavior; however, the Heun method demonstrates a higher degree of accuracy. Therefore, the Heun method is recommended for use in simulating intricate infectious disease transmission models such as COVID-19.